The Godfather part III - Coppola, Francis Ford 1939-.; Pacino, Al 1940-.; Puzo, Mario 1920-1999.; Keaton, Diane; Garcia, Andy.; Paramount Pictures Corporation; Zoetrope Studios (Hollywood, Calif. Paramount Home Video, 2002)
The Godfather part III continues the Corleane family history in 1979, as the sins of the parents are visited upon the children. Despite every attempt to go legit, to become respectable, the past cannot be silenced. The family has amassed unimaginable wealth, and as the film opens Michael Corleone(Al Pacino) is being invested with a great honor by the church. Later that day, at a reception, his daughter announces a Corleone family gift to the church and the charities of Sicily, " a check in the amount of USD100 million." But the Corleones are about to find, as others have throughout history, that you cannot buy forgiveness. Sure, you can do business with evil men inside the church, for all men are fallible and capable of sin. But God does not take payoffs.
Summary from website: http://www.dvdbeaver.com/film/dvdcompare/godfather3.htm
Based on the book by Mario Puzo.
Title from container.
Originally released as a motion picture in 1990.
Distributed in the Philippines by Magnavision Inc.
Sequel to the 1972 and 1974 films The godfather and The godfather, part II.
Writers, Francis Ford Coppola, Mario Puzo ; producers, Francis Ford Coppola, Charles Mulvehill, Fred Fuchs, Fred Roos, Gray Frederickson
Keywords: Godfather films; Mafia -- Drama; Organized crime -- Drama; Criminal behavior -- New York -- Drama; Italian American criminals -- New York -- Drama; Film sequels; Feature films